Factors That Influence The Completion Of The Final Project Of Biology Education Students At The Universitas Borneo Tarakan - Nur Fitriana Sam; Urbach Nava; Ibrahim (Universitas Pendidikan Ganesha, 2024)
Final semester students are required to write a thesis as their final project. Based on 2021 cohort data, the average study period for Biology Education Department students at the FKIP Universitas Borneo Tarakan is more than 4 years, which means students need a long time to complete their thesis. Therefore, this research aims to determine the factors influencing the preparation of students' theses at the Department of Biology Education, FKIP, Universitas Borneo Tarakan. The approach is descriptive and quantitative using a questionnaire as the main instrument and interview sheets as a supporting instrument. The sample in this research was 70 students who were programming their thesis. Data was analyzed by calculating the average percentage of each aspect. Factors that influence the preparation of a thesis consist of internal factors and external factors. Internal factors consist of aspects of motivation, intelligence, and activity. External factors consist of elements of the availability of learning resources, supervisors, peers, and parents. The results of this research show that the internal and external factors that influence students' thesis preparation are in the range of 61%-74% in the high category, meaning that students have high motivation, intelligence, and activity in working on their thesis to complete their thesis. Then the availability of learning resources and the role of support from supervisors, peers, and family are in the high category, thus influencing students to complete their thesis as soon as possible. The findings of this research have implications in practical contexts, where the results of this research can increase knowledge about the topic studied.